Students’ Learning Behavior in Writing Descriptive Texts by Using Silent Card Shuffle Strategy - Sari, Rosi Kumala; Rasmita, Rasmita (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
This research seeks to illustrate the learning behaviors of students as they compose English descriptive texts regarding local tourist attractions by utilizing the Silent Card Shuffle Strategy. The students’ skill in writing English descriptive text in English is important for Management students in designing the English tourism object brochure. Unfortunately, most of them have low motivation; inactive in English learning process. Therefore, Silent Card Shuffle Strategy is chosen by the lecturer to motivate and change the students’ learning behavior in writing English descriptive texts. The method used this research was descriptive qualitative research. The subject was 42 students on the Class 10th on semester 3 from Management Class of UPI YPTK Padang. The instruments used were observation, questionnaire, and interview. In analyzing the data, the researcher was grouped the data based on the indicator. Then, the researcher did interpreting to get the result. The researcher found that there was changing of the students’ learning behavior in writing English descriptive text because of implementation of Silent Card Shuffle Strategy. It was affected to the three aspects of the students’ behaviors; cognitive, affective and psychomotor. The researcher found this Strategy could improve students’ motivation, knowledge. They were active involved in the class discussion, focused in learning writing, active to ask questions between students in group or class discussion. Then the researcher looked the student were fun, confidence, and enthusiast and had responsibility to complete the assignment in writing descriptive text.